Genetic association and path coefficient analysis among yield and nutritional traits of tomato (Lycopersicon esculentum L.): Genetic association and path analysis in tomato (Journal of the Bangladesh Agricultural University, 2019)
The present study was conducted following randomized complete block design with three replications to evaluate the genetic variability of twenty five tomato genotypes for yield and nutritional traits and also their attributing factors. A wide range of variation was observed among the characters studied which have a great interest for tomato breeders. Heritability in broad and narrow sense for soluble solid in green and red tomato, total phenolic content, fruit diameter and seed/fruit was 93.23%, 98.58%, 99.92%, 99.37% and 96.15% respectively and for those traits, phenotypic influence was negligible. Leaf chlorophyll content and total phenolic content showed positive significant correlation with soluble solid (sugar) whereas pH showed negative correlation. Yield/plant was found highly significant and positively correlated with individual fruit weight, fruit diameter, seed/fruit, and plant height whereas soluble solid, leaf chlorophyll content, total phenolic content showed negative correlation. Path analysis revealed that soluble solid had positive direct effect with leaf chlorophyll content, pH of fruit juice and days to first flowering and negative direct effects with individual fruit weight, fruit diameter, plant height, fruit /bunch, whereas yield/plant showed positive direct effects with all above traits except soluble solids in red tomato, which clearly indicate inverse correlation between yield and nutritional components of tomato fruit. Further, principal component analysis found that four principal components contributed 75.1% of the total variability.  Individual fruit weight, days to first flowering, pH of fruit juice, fruit/bunch and soluble solids in fruits were found to be the most important traits in PC1, PC2, PC3, PC4 and PC5, respectively. As soluble solid content, yield and its component traits have high heritability, therefore, improvement is also possible using breeding approaches.J. Bangladesh Agril. Univ. 17(2): 187–193, June 2019